Henry Felix Woods and the Black Sea/Bosphorus Entrance Maritime Safety System, Then and Now - Finkel, Caroline (The Northern Mariner / Le marin du nord, 2021)
The perils of sailing in the Black Sea are legendary, and nowhere was more dangerous than the waters where the Sea and the Bosphorus meet. Vessels carrying the valuable products of the Black Sea basin to market foundered here, and in the 1860s a commission was established to look at how to reduce these losses. The article revisits its deliberations and the leading role played in establishing a maritime safety system by Navigating Lieutenant Henry Felix Woods, a Royal Navy navigation specialist. Many surviving structures of the system have been located and photographed by members of Hiking Istanbul hiking group. Les risques associés à la navigation dans la mer Noire étaient bien connus, particulièrement au confluent de la mer et du Bosphore. Des navires qui transportaient les précieux produits du bassin de la mer Noire à leur mise en marché ont sombré dans cette région. Dans les années 1860, une commission a été mise sur pied pour examiner des façons de réduire ces pertes. Le présent article revient sur ses délibérations et sur le rôle de premier plan joué dans l’établissement d’un système de sécurité maritime par le lieutenant de navigation Henry Felix Woods, spécialiste de la navigation de la Marine royale. Bon nombre des structures du système qui subsistent encore aujourd’hui ont été trouvées et photographiées par des membres du groupe de randonnée Hiking Istanbul.